Preparation method of biomass derived hard carbon negative electrode material and sodium ion battery

By using acoustic activation and gradient calcining technology in the negative electrode materials of sodium ion batteries, the pore structure of biomass-based hard carbon materials is optimized, and the problems of poor circulation stability and rate performance of existing materials are solved, achieving more efficient sodium ion storage and transfer.

CN119873816AActive Publication Date: 2025-04-25SUZHOU UNIV

Patent Information

Application Number
CN202510372021.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

The specific surface area and layer spacing of existing biomass-based hard carbon anode materials are large, resulting in poor cycling stability and rate performance of sodium ion batteries.

Method used

High-temperature pyrolysis carbon was prepared by adding biomass raw materials and oxidizing agents to the alkali liquid, performing acoustic activation treatment, and coating organic acid salts by gradient calcining, thereby optimizing the pore characteristics of the hard carbon anode material.

Benefits of technology

The sodium storage capacity of hard carbon negative electrode materials is improved, its cycle stability and rate performance are enhanced, and the consumption of electrolyte is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873816A_ABST
    Figure CN119873816A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a biomass derived hard carbon negative electrode material and a sodium ion battery, and relates to the technical field of battery energy storage. The preparation method comprises the following steps: adding a biomass raw material and an oxidizing agent into alkali liquor to obtain a hydrolysis mixed solution; carrying out acoustic activation treatment on the hydrolyzed mixed solution, and sequentially washing and drying to prepare a biomass precursor; sequentially carrying out pre-carbonization and crushing treatment on the biomass precursor to prepare low-temperature pyrolytic carbon; mixing the low-temperature pyrolytic carbon with organic acid salt to obtain a coated precursor, and performing gradient calcination on the coated precursor to obtain high-temperature pyrolytic carbon; sequentially carrying out acid pickling treatment, water washing treatment and drying treatment on the high-temperature pyrolytic carbon to prepare the hard carbon negative electrode material; wherein the gradient calcination comprises a first gradient, a second gradient and a third gradient. The hard carbon negative electrode material prepared by the method has relatively high energy storage performance, initial coulombic efficiency and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery energy storage, and in particular to a method for preparing a biomass-derived hard carbon negative electrode material and a sodium ion battery. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in new energy vehicles, portable electronic products, energy storage and other fields due to their advantages such as high energy density. However, due to the limited reserves and uneven distribution of lithium resources, their cost remains high, which has hindered the development of lithium batteries in large-scale energy storage applications. In this context, sodium-ion batteries have become a potential choice for large-scale energy storage devices because of their similar working principles to lithium-ion batteries, abundant sodium resources, low cost and good low-temperature performance.

[0003] At present, the commercialized negative electrode material of sodium-ion batteries is mainly hard carbon, and its raw materials are mainly divided into resin-based carbon and biomass-derived carbon. For example, phenol formaldehyde resin, polyacrylonitrile, starch, etc. are polymer precursors widely used to prepare hard carbon, but most polymer precursors are derived from petroleum and its derivatives, which are relatively expensive, and have a negative impact on the environment during the preparation of precursors and pyrolysis into carbon. In contrast, biomass-based raw materials are widely available, sustainable and renewable, low-pollution, and low-priced. The use of biomass to prepare hard carbon materials can not only effectively reduce costs, but also alleviate the environmental pollution caused by the large-scale incineration of waste. The unique microstructure and texture characteristics formed by biomass materials during the growth process are retained after carbonization, and their trace impurity elements (such as potassium and silicon) can activate the carbon skeleton during heat treatment and enrich the pore structure of the material. These characteristics give hard carbon excellent sodium storage performance and are expected to be widely used in sodium-ion batteries.

[0004] In the existing preparation methods of hard carbon, the inorganic elements in the biomass may increase the conductivity and interlayer spacing of the material during the carbonization process, but they may also introduce too many structural defects, resulting in excessive consumption of the electrolyte. In addition, other non-metallic impurities remaining in the hard carbon material will react with sodium ions, reducing the reversible sodium storage capacity, thereby affecting the cycle performance of the battery. Usually, the specific surface area of ​​the hard carbon material is too large, which greatly increases the contact area with the electrolyte and generates a thicker solid electrolyte interface film, further reducing the reversible sodium storage capacity. At the same time, although the larger interlayer spacing is conducive to the embedding of sodium ions, it may limit the improvement of rate performance. Overall, these defects lead to the low cycle stability and rate performance of sodium ion batteries with hard carbon negative electrode materials. Summary of the invention

[0005] One purpose of the first aspect of the present invention is to provide a method for preparing a biomass-derived hard carbon negative electrode material, so as to solve the technical problem in the prior art that the biomass-based hard carbon negative electrode material has a large specific surface area and interlayer spacing, resulting in poor cycle stability and rate performance of sodium ion batteries.

[0006] Another object of the first aspect of the present invention is to further increase the hydrolysis rate of biomass raw materials.

[0007] The second aspect of the present invention aims to provide a sodium ion battery comprising a hard carbon negative electrode material prepared by the preparation method of the hard carbon negative electrode material.

[0008] According to the purpose of the present invention, the present invention provides a method for preparing a biomass-derived hard carbon negative electrode material, comprising the following steps: adding a biomass raw material and an oxidant into an alkaline solution to obtain a hydrolysis mixed solution; The hydrolyzed mixed solution is subjected to acoustic activation treatment, and then washed and dried in sequence to prepare a biomass precursor; The biomass precursor is sequentially pre-carbonized and pulverized to prepare low-temperature pyrolytic carbon; The low-temperature pyrolytic carbon is mixed with an organic acid salt to obtain a coating precursor, and the coating precursor is subjected to gradient calcination to obtain high-temperature pyrolytic carbon; The high temperature pyrolysis carbon is sequentially subjected to acid washing, water washing and drying to prepare a hard carbon negative electrode material; wherein: The gradient calcination includes a first gradient, a second gradient and a third gradient. The calcination temperature of the first gradient is the melting temperature of the organic acid salt, the calcination temperature of the second gradient is the reduction temperature or decomposition temperature of the metal oxide or metal carbonate, and the calcination temperature of the third gradient is the molding temperature of the hard carbon negative electrode material and the metal gasification temperature.

[0009] Optionally, the mass ratio of the organic acid salt to the low-temperature pyrolysis carbon is any value between 1 wt% and 20 wt%.

[0010] Optionally, the organic acid salt is a mixture of any one or more of gluconate, acetate, citrate or lactate.

[0011] Optionally, the gluconate is at least one of zinc gluconate, calcium gluconate, magnesium gluconate, potassium gluconate, ferrous gluconate, and magnesium gluconate; The acetate is at least one of zinc acetate, calcium acetate, potassium acetate and magnesium acetate; The citrate is at least one of zinc citrate, calcium citrate and potassium citrate; The lactate is at least one of zinc lactate, calcium lactate, potassium lactate and magnesium lactate.

[0012] Optionally, the mass ratio of the oxidant to the biomass raw material is any value between 3wt% and 10wt%.

[0013] Optionally, the oxidant is a mixture of any one or more of hydrogen peroxide, hypochlorite, and persulfate.

[0014] Optionally, the concentration of the alkali solution is any value between 0.5 mol / L and 3 mol / L, and the temperature of the alkali solution is any value between 40° C. and 100° C.

[0015] Optionally, the alkali solution is an aqueous solution of one or more mixtures of metal hydroxides or metal carbonates.

[0016] Optionally, the biomass raw material is a mixture of any one or more of bamboo, wood, reed, coffee grounds, bagasse, wheat straw, rice straw, corn straw, rice sticks, coconut shells, durian shells, rice shells, hazelnut shells, starch, lignin, etc.

[0017] According to the purpose of the second aspect of the present invention, the present invention also provides a sodium ion battery, which comprises a hard carbon negative electrode material prepared by any of the above preparation methods.

[0018] The present invention achieves a synergistic effect by adding biomass raw materials and oxidants to alkaline solution, performing acoustic activation treatment on the hydrolysis mixed solution, and gradient calcining the coated precursor coated with an organic acid salt, so that the oxidant forms highly oxidizing active oxygen species under alkaline conditions. The active oxygen destroys the chemical bonds in lignin and hemicellulose through oxidation, and the acoustic activation treatment can significantly enhance the mass transfer and diffusion performance of the alkaline solution, promote the alkali solution and active oxygen species to penetrate into the fiber tissue or carbon interlayer and carbon pores, promote the hydrolysis reaction rate of the molecular structure in the biomass raw material, reduce the relative content of lignin and hemicellulose while increasing the relative content of cellulose, increase the graphite domain area after high-temperature carbonization, and while increasing the degree of graphitization, the graphite domain shrinks and entangles at high temperature, promoting the generation of closed pores, thereby increasing the sodium storage capacity of the hard carbon platform area, and the gradient calcination of the coated precursor can promote the filling and encapsulation of the hard carbon open pores and the etching of nanopores after filling, thereby optimizing the pore characteristics of the hard carbon negative electrode material, improving its sodium storage performance, and improving the cycle stability and rate performance.

[0019] Furthermore, the temperature of the alkali solution of the present invention is any value between 40°C and 100°C. By setting the temperature of the alkali solution within the above range, the hydrolysis rate of the biomass raw material can be increased, the reaction time can be reduced, and the process of the carbon negative electrode material can be shortened.

[0020] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings: Figure 1 is a schematic flow chart of a method for preparing a hard carbon negative electrode material according to an embodiment of the present invention; Figure 2 is the XRD spectrum of the biomass precursor in Example 1 and Comparative Examples 1-4 of the present invention; Figure 3 is the XRD spectrum of the hard carbon negative electrode material prepared in Example 1 and Comparative Examples 1-4 of the present invention; Figure 4 is a SEM image of the hard carbon negative electrode material prepared according to Example 1 of the present invention; Figure 5 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Example 1 of the present invention; Figure 6 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Example 2 of the present invention; Figure 7 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Example 3 of the present invention; Figure 8 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Example 4 of the present invention; Fig. 9 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Comparative Example 1 of the present invention; Fig.10 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Comparative Example 2 of the present invention; Fig.11 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Comparative Example 3 of the present invention; Fig.12 This is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0022] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0023] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0024] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0026] Figure 1 is a schematic flow chart of a method for preparing a hard carbon negative electrode material according to an embodiment of the present invention, Figure 2 is the XRD pattern of the biomass precursor in Example 1 and Comparative Examples 1-4 of the present invention, Figure 3 is the XRD spectrum of the hard carbon negative electrode material prepared in Example 1 and Comparative Examples 1-4 of the present invention, Figure 4 is a SEM image of the hard carbon negative electrode material prepared according to Example 1 of the present invention, Figure 5 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Example 1 of the present invention, Figure 6 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Example 2 of the present invention, Figure 7 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Example 3 of the present invention, Figure 8 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Example 4 of the present invention, Fig. 9 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Comparative Example 1 of the present invention, Fig.10 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Comparative Example 2 of the present invention, Fig.11 is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Comparative Example 3 of the present invention, Fig.12 This is the first charge and discharge curve of the hard carbon negative electrode material prepared according to Comparative Example 4 of the present invention.

[0027] like Figure 1 As shown, the present invention provides a method for preparing a biomass-derived hard carbon negative electrode material, comprising the following steps: Step S100: adding a biomass raw material and an oxidant into an alkaline solution to obtain a hydrolysis mixed solution; Step S200: performing acoustic activation treatment on the hydrolyzed mixed solution, and sequentially washing and drying the solution to prepare a biomass precursor; Step S300: pre-carbonizing and pulverizing the biomass precursor in sequence to prepare low-temperature pyrolytic carbon; Step S400: mixing low-temperature pyrolytic carbon with an organic acid salt to obtain a coating precursor, and performing gradient calcination on the coating precursor to obtain high-temperature pyrolytic carbon; Step S500: The high-temperature pyrolysis carbon is subjected to acid washing, water washing and drying treatment to prepare a hard carbon negative electrode material; wherein the gradient calcination includes a first gradient, a second gradient and a third gradient, the calcination temperature of the first gradient is the melting temperature of the organic acid salt, the calcination temperature of the second gradient is the reduction temperature or decomposition temperature of the metal oxide or metal carbonate, and the calcination temperature of the third gradient is the molding temperature of the hard carbon negative electrode material and the metal gasification temperature.

[0028] In this embodiment, in the preparation method of biomass-derived hard carbon negative electrode material, the biomass raw material and the oxidant are first added to an alkaline solution and mixed evenly to obtain a hydrolysis mixed solution, the hydrolysis mixed solution is subjected to acoustic activation treatment, and is washed and dried in sequence to prepare a biomass precursor, the biomass precursor is pre-carbonized and pulverized in sequence to obtain low-temperature pyrolytic carbon, the low-temperature pyrolytic carbon is mixed with an organic acid salt to obtain a coated precursor, the coated precursor is gradient calcined to obtain high-temperature pyrolytic carbon, the high-temperature pyrolytic carbon is acid-washed, water-washed and dried to obtain a hard carbon negative electrode material.

[0029] In this embodiment, the synergistic effect of adding biomass raw materials and oxidants to alkaline solution, acoustically activating the hydrolysis mixed solution, and gradient calcining the coated precursor coated with an organic acid salt is achieved, so that the oxidant forms highly oxidizing active oxygen species under alkaline conditions. The active oxygen destroys the chemical bonds in lignin and hemicellulose through oxidation, and the acoustic activation treatment can significantly enhance the mass transfer and diffusion properties of the alkaline solution, promote the alkali solution and active oxygen species to penetrate into the fiber tissue or carbon interlayer and carbon pores, promote the hydrolysis reaction rate of the molecular structure in the biomass raw material, reduce the relative content of lignin and hemicellulose while increasing the relative content of cellulose, increase the graphite domain area after high-temperature carbonization, and while increasing the degree of graphitization, the graphite domains shrink and entangle at high temperature, promote the formation of closed pores, and thereby increase the sodium storage capacity of the hard carbon platform area. The gradient calcination of the coated precursor can promote the filling and encapsulation of the hard carbon open pores, and the etching of nanopores after filling, thereby optimizing the pore characteristics of the hard carbon negative electrode material, improving its sodium storage performance, and improving the cycle stability and rate performance.

[0030] In this embodiment, the biomass raw material is hydrolyzed in a mixed solution of an oxidant and an alkali solution to regulate the composition of the biomass precursor and increase the relative content of cellulose in the biomass precursor, thereby increasing the graphite domain area after high-temperature carbonization, increasing the number of closed pores in the graphite domain area, and then increasing the degree of graphitization, so as to improve the electronic and ionic conductivity of the hard carbon negative electrode material. A higher number of closed pores can increase the filling sodium storage capacity of the hard carbon, thereby increasing the sodium storage capacity of the hard carbon platform area, thereby significantly improving the electrochemical properties of the hard carbon negative electrode material.

[0031] In this embodiment, a strong oxidant is used to pre-oxidize and carbonize the biomass, and oxygen-rich functional groups are introduced on the carbon surface, which effectively improves the interfacial compatibility of the hard carbon negative electrode material and enhances the wettability of the electrolyte to the hard carbon, thereby promoting the transmission of electrolyte ions on the electrode surface and optimizing the electrochemical reaction kinetics. In addition, the oxygen-rich functional groups can serve as active sites to provide reaction sites for subsequent coating, composite or doping, thereby further regulating the physical and chemical properties of the hard carbon negative electrode material to optimize its sodium storage performance and rate performance.

[0032] In the present embodiment, the acoustic activation treatment comprises activation treatment and standing treatment performed multiple times at intervals and each activation treatment is followed by standing treatment, the activation time is any value between 3 min and 9 min, the standing time is any value between 1 min and 7 min, and the total acoustic activation treatment time is any value between 15 min and 60 min. The acoustic activation treatment is performed by alternating activation treatment and standing treatment on the hydrolysis mixed solution, so that the alkali solution and the active oxygen species can not only continuously penetrate into the molecular structure of the biomass raw material, but also stay in the molecular structure of the biomass raw material at different depths for a standing time, so that the alkali solution and the active oxygen can act on the molecular structure of the biomass raw material at different depths, thereby further promoting the hydrolysis reaction of the biomass raw material, so that the biomass raw material can be completely hydrolyzed. Here, the activation time can be 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min, or any value between 3 min and 9 min. The standing time can be 1 min, 2 min, 3 min, 4 min, 5 min, 6 min or 7 min, or any value between 1 min and 7 min. The total time of the acoustic activation treatment can be 15 min, 20 min, 25 min, 30 min, 40 min, 50 min or 60 min, or any value between 15 min and 60 min.

[0033] In this embodiment, during the acoustic activation treatment, the hydrolysis mixed solution can generate tiny bubbles under the cavitation effect of ultrasound, and the bubbles rapidly expand and burst under the action of sound waves, forming a local high temperature and high pressure environment, which can promote the destruction of the molecular structure of the biomass raw material, promote its decomposition and hydrolysis reaction. In addition, it can also promote the increase of the contact area between the biomass raw material and the alkaline solution, promote the reaction rate of the biomass raw material and the alkaline solution, and greatly shorten the hydrolysis reaction time.

[0034] In this embodiment, the sound wave frequency of the acoustic activation treatment in step S200 is any value in the range of 20kHz-100kHz, and the power is any value in the range of 300W-1000W, that is, the sound wave frequency of the acoustic activation treatment can be 20kHz, 30kHz, 40kHz, 70kHz, 90kHz or 100kHz, or any value in the range of 20kHz-100kHz, and the power can be 300W, 400W, 500W, 700W, 900W or 1000W, or any value in the range of 300W-1000W. By setting the sound wave frequency and power of the acoustic activation treatment within the above range, it is ensured that the alkali solution and the active oxygen are uniformly penetrated into all parts of the biomass raw material, so that the biomass raw material is completely hydrolyzed, and the distribution uniformity of the pore structure of the hard carbon after high-temperature carbonization is improved, thereby improving the specific capacity, reducing structural defects, and improving the first coulomb efficiency and cycle life.

[0035] In this embodiment, in step S200, the product after the acoustic activation treatment is washed with clean water until the pH of the product is less than 9.0 and then dried. By removing the residual alkaline solution in the hydrolyzed product of the biomass raw material, the purity of the biomass precursor is improved, thereby improving the degree of graphitization after high-temperature carbonization, and preventing excessive alkaline substances from causing alkaline crystals to form in the biomass precursor after the product is dried, thereby preventing the formation of the pore structure of the hard carbon negative electrode material. That is, by washing the product after the acoustic activation treatment to a pH less than 9.0, it can be ensured that there is no high concentration of alkaline salts on the surface of the biomass precursor, thereby forming a uniformly distributed pore structure during the carbonization process and optimizing the sodium storage channel.

[0036] In this embodiment, the drying temperature is any value between 60°C and 180°C, and the drying time is any value between 1h and 12h, that is, the drying temperature can be 60°C, 80°C, 100°C, 120°C, 150°C or 180°C, or any value between 60°C and 180°C, and the drying time can be 1h, 2h, 3h, 5h, 7h, 10h or 12h, or any value between 1h and 12h. By setting the drying temperature and drying time within the above range, the biomass precursor containing a large amount of water is prevented from directly entering the carbonization step, and the rapid vaporization of water causes the material to crack, uneven holes, and even local sintering, thereby improving the uniformity of carbonization, avoiding the collapse of the pore structure, and improving the specific capacity. At the same time, it is avoided that the drying temperature is too high or the drying time is too long to destroy the cellulose structure formed by hydrolysis, or the drying temperature is too low or the drying time is too short to achieve the effect of removing water from the biomass precursor, thereby further improving the purity of the biomass precursor.

[0037] In this embodiment, the biomass precursor is pre-carbonized so that the biomass precursor is pre-carbonized at a relatively low temperature to form a carbon morphology, so as to facilitate subsequent pore filling, coating or other treatment and modification.

[0038] In this embodiment, the calcination temperature of the first gradient is the melting temperature of the organic acid salt, so that the organic acid salt melts and diffuses into the open pore area of ​​the hard carbon to fill the nanopores of the low-temperature pyrolytic carbon and form a preliminary sealing structure, which initially reduces the structural defects and specific surface area of ​​the hard carbon negative electrode material, prevents excessive shrinkage or structural collapse of the material during subsequent calcination, and improves the integrity of the carbon skeleton. The molten organic acid salt forms a uniform coating on the surface of the hard carbon, so that a uniform protective layer is formed on the material surface of the low-temperature pyrolytic carbon to prevent particle agglomeration.

[0039] In this embodiment, the calcination temperature of the first gradient is any value between 150°C and 200°C, the heating rate is 1°C / min-10°C / min, and the holding time is any value between 0.5h and 6h, that is, the calcination temperature of the first gradient is 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, or any value between 150°C and 200°C, the heating rate can be 1°C / min, 3°C / min, 5°C / min, 7°C / min, 9°C / min or 10°C / min, or 1°C / min-10°C / min, and the holding time can be 0.5h, 1h, 3h, 5h or 6h, or any value between 0.5h and 6h. By setting the calcination temperature, heating rate and holding time of the first gradient within the above range, it is helpful for the organic acid salt to be completely melted and filled into the cavities of the low-temperature pyrolytic carbon to reduce structural defects and specific surface area, and at the same time, the molten organic acid salt is uniformly coated on the surface of the low-temperature pyrolytic carbon to further fill the pores, thereby improving the structural uniformity of the low-temperature pyrolytic carbon and optimizing the distribution of sodium storage sites. At the same time, it prevents the calcination temperature of the first gradient from being too low, resulting in the organic acid salt not being completely melted, and the holding time from being too short, resulting in the molten organic acid salt not being fully filled into the pores and closing the pores. It can also avoid the situation where the calcination temperature of the first gradient is too high, resulting in the metal in the organic acid salt being decomposed or gasified prematurely, resulting in the inability to fill the pores.

[0040] In this embodiment, the calcination temperature of the second gradient is the reduction temperature or decomposition temperature of the metal oxide or metal carbonate, that is, under the calcination temperature condition of the second gradient, the metal carbonate in the organic acid salt decomposes, releasing carbon dioxide gas and metal oxide, and the released carbon dioxide gas forms nanoscale channels inside the hard carbon, optimizing the sodium storage capacity of the material, and part of the metal oxide is reduced or partially converted into gaseous metal to further optimize and control the pore structure, increase the ion diffusion rate, and improve the rate performance. At the same time, under the above temperature conditions, it is also possible to remove some volatile organic matter, improve the stability of the carbon skeleton, make it more conducive to the embedding of sodium ions, thereby improving the specific capacity of the hard carbon negative electrode material.

[0041] In this embodiment, the calcination temperature of the second gradient is any value between 700°C and 900°C, the heating rate is 1°C / min-10°C / min, and the holding time is any value between 0.5h and 6h, that is, the calcination temperature of the second gradient is 700°C, 750°C, 800°C, 850°C or 900°C, or any value between 700°C and 900°C, the heating rate can be 1°C / min, 3°C / min, 5°C / min, 7°C / min, 9°C / min or 10°C / min, or 1°C / min-10°C / min, and the holding time can be 0.5h, 1h, 3h, 5h or 6h, or any value between 0.5h and 6h. By setting the calcination temperature, heating rate and holding time of the second gradient within the above range, it is helpful to completely decompose the metal carbonate into metal oxide or reduce it to metal, so as to preliminarily optimize the pore structure of the low-temperature pyrolytic carbon under the calcination temperature condition of the second gradient, increase the number of nanopores while preventing structural defects caused by the formation of large holes, thereby increasing the sodium storage sites of the hard carbon negative electrode material while reducing structural defects. In addition, setting the heating rate within the above range can prevent the calcination temperature of the second gradient from rising too fast, resulting in uneven decomposition of the metal carbonate / oxide, thereby affecting the stability of the pore structure, and can also prevent the structure between the carbon layers from being too densely stacked, affecting the interlayer spacing, or forming a local over-graphitized area, affecting the electronic conductivity of the overall hard carbon negative electrode material.

[0042] In this embodiment, since the third gradient calcination temperature is the key temperature for the final formation of the hard carbon negative electrode material, the disordered arrangement between the carbon layers is optimized to form a short-range ordered structure or a long-range disordered structure suitable for sodium storage, and the third gradient calcination temperature is used as the metal vaporization temperature, the metal in the organic acid salt is vaporized under the temperature condition of the third gradient, and more nanopores are etched, further optimizing the pore structure of the hard carbon negative electrode material, ensuring the reversible insertion or extraction of sodium ions. In addition, the third gradient calcination temperature can promote the short-range ordering of the hard carbon material, improve its electronic conductivity, optimize the rate performance, and enhance the cycle life.

[0043] In this embodiment, the calcination temperature of the third gradient is any value between 1100°C and 1700°C, the heating rate is 1°C / min-10°C / min, and the holding time is any value between 1h and 12h, that is, the calcination temperature of the third gradient is 1100°C, 1200°C, 1300°C, 1500°C or 1700°C, or any value between 1100°C and 1700°C, the heating rate can be 1°C / min, 3°C / min, 5°C / min, 7°C / min, 9°C / min or 10°C / min, or 1°C / min-10°C / min, and the holding time can be 1h, 3h, 5h, 10h or 12h, or any value between 1h and 12h. By setting the calcination temperature, heating rate and holding time of the third gradient within the above range, it helps to disorder the arrangement and final forming of the carbon layers in the hard carbon negative electrode material, prevents the local graphitization of the hard carbon negative electrode material caused by the heating rate being too fast, and reduces the electronic conductivity. At the same time, it prevents the structural instability of the hard carbon negative electrode material or the incomplete gasification of the metal caused by the holding time being too short, which affects the specific capacity and pore structure, thereby avoiding affecting the sodium storage performance of the hard carbon negative electrode material.

[0044] In this embodiment, the pickling treatment in step S500 is to mix and stir the high-temperature pyrolysis carbon with acid solution to remove the original metal ash of the biomass and the metal impurities remaining from the etching of organic acid salts. Here, the concentration of the acid solution is any value from 1mol / L to 5mol / L, the concentration of the acid solution can be 1mol / L, 2mol / L, 3mol / L, 4mol / L or 5mol / L, or any value from 1mol / L to 5mol / L, the pickling temperature is any value from 25℃ to 80℃, the pickling temperature can be 25℃, 30℃, 40℃, 60℃ or 80℃, or any value from 25℃ to 80℃, the pickling time is any value from 0.2h to 8h, the pickling time can be 0.2h, 0.5h, 1h, 2h, 4h or 8h, or any value from 0.2h to 8h, and the acid solution is any one or more of sulfuric acid, nitric acid, hydrochloric acid, acetic acid, formic acid, citric acid, and phosphoric acid.

[0045] In this embodiment, the drying temperature is any value between 100°C and 200°C, and the drying time is any value between 1h and 24h. The drying temperature is set to be higher than the boiling point of water to completely remove the moisture in the high-temperature pyrolytic carbon, and the drying time is set within the above range to fully dry the high-temperature pyrolytic carbon. Here, the drying temperature can be 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, or any value between 100°C and 200°C, and the drying time can be 1h, 2h, 5h, 10h, 15h, 20h or 24h, or any value between 1h and 24h.

[0046] In a further embodiment, the mass ratio of the organic acid salt to the low-temperature pyrolytic carbon is any value in the range of 1wt%-20wt%, that is, the mass ratio of the organic acid salt to the low-temperature pyrolytic carbon can be 1wt%, 2wt%, 5wt%, 10wt%, 12wt%, 15wt%, 17wt% or 20wt%, or any value in the range of 1wt%-20wt%. By setting the mass ratio of the organic acid salt to the low-temperature pyrolytic carbon within the above range, metal induced etching can be optimized, the uniformity of the pore structure can be improved, and the sodium storage active sites can be increased.

[0047] In a preferred embodiment, the mass ratio of the organic acid salt to the low-temperature pyrolytic carbon is any value between 5wt% and 15wt% to form a uniform coating, optimize pores, improve specific capacity, optimize rate performance, and improve first coulombic efficiency. Here, the mass ratio of the organic acid salt to the low-temperature pyrolytic carbon can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, or any value between 5wt% and 15wt%.

[0048] In a further embodiment, the organic acid salt is a mixture of any one or more of gluconate, acetate, citrate or lactate, that is, the organic acid salt can be a single organic acid salt or a mixture of multiple organic acid salts. Different types of organic acid salts are suitable for calcination and pore size optimization under different temperature conditions, that is, the melting temperatures of different organic acid salts, the decomposition temperatures and gasification temperatures of metal carbonates, and the decomposition temperatures or metal gasification temperatures of metal oxides are all different, and organic salts of different components can also regulate different pore sizes. The corresponding one or more organic acid salt compositions can be selected according to needs to coat the low-temperature pyrolytic carbon.

[0049] In a further embodiment, gluconate is at least one of zinc gluconate, calcium gluconate, magnesium gluconate, potassium gluconate, ferrous gluconate, and magnesium gluconate; acetate is at least one of zinc acetate, calcium acetate, potassium acetate, and magnesium acetate; citrate is at least one of zinc citrate, calcium citrate, and potassium citrate; and lactate is at least one of zinc lactate, calcium lactate, potassium lactate, and magnesium lactate. That is, gluconate, acetate, citrate, or lactate in the organic acid salt all include metal carbonates of multiple different metal types, which can be applied to different calcination temperatures and pore size regulation.

[0050] In a further embodiment, the mass ratio of the oxidant to the biomass raw material is any value in the range of 3wt%-10wt%, that is, the mass ratio of the oxidant to the biomass raw material can be 3wt%, 4wt%, 5wt%, 7wt% or 10wt%, or any value in the range of 3wt%-10wt%. By setting the mass ratio of the oxidant to the biomass raw material within the above range, it is possible to effectively promote the full hydrolysis of the biomass raw material and regulate the surface functional groups of the biomass raw material to improve the sodium affinity of the carbon material while preventing the excessive addition of the oxidant from causing excessive pores and increasing the specific surface area, affecting the initial coulombic efficiency, and even causing excessive damage to the carbon skeleton, thereby reducing the mechanical strength of the hard carbon negative electrode material and affecting the cycle life.

[0051] In a further embodiment, the oxidant is a mixture of any one or more of hydrogen peroxide, hypochlorite, and persulfate. Different types of oxidants have different oxidizing properties and are selected according to the pore size that needs to be regulated in the hard carbon negative electrode material and the cellulose content in the biomass precursor.

[0052] In a further embodiment, the concentration of the alkali solution is any value between 0.5mol / L and 3mol / L, that is, the concentration of the alkali solution can be 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L or 3mol / L, or any value between 0.5mol / L and 3mol / L. By setting the concentration of the alkali solution within the above range, the alkali solution can promote the hydrolysis of hemicellulose and part of lignin in the biomass, increase the reactivity of cellulose, and introduce functional groups such as hydroxyl groups and ether bonds on the surface of the biomass to increase the polarity of the carbon material, which helps the electrolyte to infiltrate sodium ions for storage, increase the sodium ion migration rate, optimize the rate performance, and reduce the irreversible capacity loss.

[0053] In a further embodiment, the alkali solution is an aqueous solution of one or more mixtures of metal hydroxides or metal carbonates. In the preparation process of hard carbon negative electrode materials, the use of aqueous solutions of metal hydroxides or metal carbonates as alkali solutions can effectively regulate the hydrolysis process, pore structure and final electrochemical properties of biomass. In addition, different types of metal hydroxides and metal carbonates have different alkalinity and reaction characteristics. Through reasonable mixing and use, the specific capacity, rate performance and cycle stability of hard carbon negative electrode materials can be further optimized. Here, the metal hydroxide can be sodium hydroxide or potassium hydroxide, and the metal carbonate can be sodium carbonate or potassium carbonate.

[0054] In a further embodiment, the temperature of the alkali solution is any value between 40°C and 100°C, that is, the temperature of the alkali solution can be 40°C, 50°C, 60°C, 80°C or 100°C, or any value between 40°C and 100°C. By setting the temperature of the alkali solution within the above range, the hydrolysis rate of the biomass raw material can be increased, the reaction time can be reduced, and the process of the carbon negative electrode material can be shortened.

[0055] In a further embodiment, the biomass raw material is a mixture of any one or more of bamboo, wood, reed, coffee grounds, bagasse, wheat straw, rice straw, corn straw, rice stick, coconut shell, durian shell, rice shell, hazelnut shell, starch, lignin, etc. The different proportions of cellulose, hemicellulose and lignin in the above-mentioned various biomass raw materials determine the interlayer structure and pore distribution of hard carbon during the carbonization process. By selecting different biomass raw materials, the sodium storage site can be optimized and the specific capacity can be improved.

[0056] The present invention also provides a sodium ion battery, which includes a biomass-derived hard carbon negative electrode material as a negative electrode active material, and the sodium ion battery has an initial discharge specific capacity higher than 358 mAh / g, an initial coulombic efficiency greater than 92.4%, and a capacity retention rate of 2000 cycles higher than 91.3%. The preparation method of the hard carbon negative electrode material is not described in detail here.

[0057] In this embodiment, in the preparation method of the sodium ion battery, the hard carbon negative electrode material prepared in the above embodiment is used as the negative electrode active material. The negative electrode active material, the conductive agent, the first adhesive and the second adhesive are weighed according to the mass ratio of 95:2:2:1, and then deionized water is added and stirred for 6 hours to obtain a uniform black slurry. The black slurry is in a viscous slurry state. The above black slurry is evenly coated on the copper foil, and then vacuum dried at 80°C for 6 hours to obtain a pole piece with uniform thickness, and then the pole piece is punched into a disc with a diameter of 14 mm as the negative electrode. A metal disc with a diameter of 14 mm is used as the negative electrode, glass fiber is used as the diaphragm, and 1 mol / L NaPF6 is used as the electrolyte. A CR2025 button battery is assembled in a glove box filled with argon gas, and the battery is left to stand for 24 hours before the charge and discharge performance test is performed. Here, the conductive agent is acetylene black, the first adhesive is sodium carboxymethyl cellulose, and the second adhesive is styrene-butadiene rubber.

[0058] The present application will be further described in detail below with reference to specific embodiments.

[0059] Example 1 After selecting bamboo powder through a 50-mesh sieve, pour it into a 3mol / L sodium hydroxide solution, add sodium hypochlorite with a mass fraction of 5wt% of the bamboo powder, and sonicate at 75°C. The sonic wave frequency is 100kHz, the power is 1000W, and it is left to stand for 1min every 9min of activation. The total time of sonication and standing is 60min. Then, it is taken out, filtered, washed to neutrality, and dried to obtain a biomass precursor. The biomass precursor is heated to 600°C at 5°C / min in a pyrolysis furnace in a nitrogen atmosphere for 2h, then cooled naturally, and crushed to obtain low-temperature pyrolytic carbon. The low-temperature pyrolytic carbon is fully mixed with zinc lactate with a mass fraction of 20wt%. Then, it is heated to 200°C at 5°C / min in a tubular furnace in a nitrogen atmosphere for 1h, then heated to 800°C at 5°C / min for 2h, then heated to 1200°C at 5°C / min for 2h, and then cooled naturally to obtain high-temperature pyrolytic carbon. The high-temperature pyrolysis carbon was stirred with a 5 mol / L hydrochloric acid solution at 80°C for 10 min, then washed with water until neutral, and then dried at 100°C for 1 h to prepare a biomass-derived hard carbon negative electrode material.

[0060] Example 2 After selecting bamboo powder through a 50-mesh sieve, pour it into a 0.5 mol / L sodium hydroxide solution, add sodium hypochlorite with a mass fraction of 3 wt% of the bamboo powder, and perform acoustic activation and infiltration at 75 °C. The acoustic wave frequency is 20 kHz and the power is 450 W. After each activation treatment for 3 minutes, the solution is left to stand for 2 minutes. The total time for acoustic activation and standing treatment is 15 minutes. Then, the solution is taken out, filtered, washed to neutrality, and dried to obtain a biomass precursor. The biomass precursor is heated to 800 °C at 20 °C / min in a pyrolysis furnace in a nitrogen atmosphere for 1 hour, then cooled naturally, and crushed to obtain low-temperature pyrolytic carbon. The low-temperature pyrolytic carbon is fully mixed with zinc lactate with a mass fraction of 1 wt%. Then, the solution is heated to 200 °C at 5 °C / min in a tubular furnace in a nitrogen atmosphere for 1 hour, then heated to 800 °C at 10 °C / min for 2 hours, then heated to 1200 °C at 5 °C / min for 2 hours, and then cooled naturally to obtain high-temperature pyrolytic carbon. The high-temperature pyrolysis carbon was stirred with a 5 mol / L hydrochloric acid solution at 25°C for 10 min, then washed with water until neutral, and then dried at 200°C for 1 h to prepare a biomass-derived hard carbon negative electrode material.

[0061] Example 3 After selecting bamboo powder with a 150-mesh sieve, pour it into a 3 mol / L sodium hydroxide solution, add sodium hypochlorite with a mass fraction of 10 wt% of bamboo powder, and sonicate at 40 ° C. The sonic wave frequency is 20 kHz, the power is 450 W, and it is left to stand for 1 min for every 5 min of activation. The total time of sonication and standing is 45 min. Then, it is taken out, filtered, washed to neutrality, and dried to obtain a biomass precursor. The biomass precursor is heated to 400 ° C at 5 ° C / min in a pyrolysis furnace in a nitrogen atmosphere for 24 h, then cooled naturally, and crushed to obtain low-temperature pyrolytic carbon. The low-temperature pyrolytic carbon is fully mixed with zinc gluconate with a mass fraction of 20 wt%. Then, it is heated to 180 ° C at 1 ° C / min in a tubular furnace in a nitrogen atmosphere for 1 h, then heated to 800 ° C at 10 ° C / min for 2 h, and then heated to 1100 ° C at 10 ° C / min for 3 h, and high-temperature pyrolytic carbon is obtained after natural cooling. The high-temperature pyrolysis carbon was stirred with 1 mol / L hydrochloric acid solution at 25°C for 4 hours, then washed with water until neutral, and then dried at 120°C for 6 hours to prepare a biomass-derived hard carbon negative electrode material.

[0062] Example 4 After selecting bamboo powder with a 150-mesh sieve, pour it into a 1mol / L sodium hydroxide solution, add sodium hypochlorite with a mass fraction of 10wt% of the bamboo powder, and sonicate at 40°C. The sonic wave frequency is 20kHz, the power is 450W, and it is left to stand for 1min for every 4min of activation. The total time of sonication and standing is 30min. Then, it is taken out, filtered, washed to neutrality, and dried to obtain a biomass precursor. The biomass precursor is heated to 400°C at 5°C / min in a pyrolysis furnace in a nitrogen atmosphere for 2h, then cooled naturally, and crushed to obtain low-temperature pyrolytic carbon. The low-temperature pyrolytic carbon is fully mixed with zinc gluconate with a mass fraction of 10wt%. Then, it is heated to 180°C at 5°C / min in a tubular furnace in a nitrogen atmosphere for 1h, then heated to 800°C at 5°C / min for 2h, then heated to 1700°C at 5°C / min for 1h, and then cooled naturally to obtain high-temperature pyrolytic carbon. The high-temperature pyrolysis carbon was stirred with 1 mol / L hydrochloric acid solution at 25°C for 4 hours, then washed with water until neutral, and then dried at 120°C for 6 hours to prepare a biomass-derived hard carbon negative electrode material.

[0063] Example 5 The only difference between Example 5 and Example 1 is that during the sonication treatment, the process was left standing for 1 minute for every 4 minutes of activation, the total time of sonication treatment and standing was 45 minutes, and the mass fraction of zinc lactate was 10 wt %.

[0064] Example 6 The only difference between Example 6 and Example 1 is that the biomass raw material is waste wood pieces with a size less than 5 mm.

[0065] Example 7 The only difference between Example 7 and Example 1 is that the biomass raw material is 100-mesh coconut shell powder.

[0066] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the 50-mesh biomass raw material is directly pre-carbonized.

[0067] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the hydrolyzed mixed solution is not subjected to acoustic activation treatment.

[0068] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that sodium hypochlorite is not included in the hydrolysis mixed solution.

[0069] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the low-temperature pyrolytic carbon is not coated with zinc lactate and carbonized and etched.

[0070] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the bamboo powder and the alkali solution are first mixed and reacted for a preset time, and then the oxidant is added to the reaction solution.

[0071] The hard carbon negative electrode materials prepared in Examples 1-7 and Comparative Examples 1-5 were used as negative electrode active materials of corresponding sodium ion batteries, and the electrochemical performance of the sodium ion batteries prepared based on the hard carbon negative electrode materials prepared in Examples 1-7 and Comparative Examples 1-5 was tested to obtain the electrochemical performance test result graph shown in Table 1. Here, the test temperature in the electrochemical performance test is 25° C., and the charge and discharge cut-off voltage is 0.01-2.5V.

[0072]

[0073] As shown in Table 1, the hard carbon negative electrode materials prepared in Examples 1-7 as negative electrode active materials of sodium ion batteries can make the first charge specific capacity of the corresponding sodium ion batteries higher than 358.61mAh / g, the first coulomb efficiency higher than 92.4%, the first discharge specific capacity of the cycle at a current density of 1A / g higher than 330.61mAh / g, and the capacity retention rate of 2000 cycles at a current density of 1A / g higher than 91.3%. Compared with the hard carbon negative electrode materials prepared in Comparative Examples 1-5 as negative electrode active materials of sodium ion batteries, the sodium ion batteries prepared by the hard carbon negative electrode materials prepared in Examples 1-7 of the present invention all have significantly improved discharge specific capacity, first coulomb efficiency and rate performance.

[0074] As shown in Table 1, the first discharge specific capacity, first coulombic efficiency and capacity retention rate in Comparative Example 1 are significantly lower than the corresponding electrochemical performance parameters of Example 1, indicating that in Comparative Example 1, the biomass raw materials are subjected to alkali solution treatment and oxidation treatment separately, and the biomass raw materials cannot be completely hydrolyzed, resulting in the electrochemical performance of the sodium ion battery made from the product prepared in Comparative Example 1 being significantly lower than the relevant electrochemical performance of the hard carbon negative electrode material prepared in Example 1.

[0075] like Figure 2 As shown, Figure 2 It is the XRD spectrum of the biomass precursor after the treatment of step S200 in Example 1 and Comparative Examples 1-4, including the (002) peak at 2θ=22.5° and the am peak at 2θ=18°. The peak of the (002) peak is the diffraction peak of the cellulose crystal region, and the am peak is the diffuse diffraction peak of the amorphous region. The (002) peak intensity of Example 1 and Comparative Example 4 is high, the peak shape is sharp, and the (002) peak and the am peak together indicate that the biomass precursor cellulose has high crystallinity, and the components such as lignin and hemicellulose are fully removed. The (002) peak intensity of Comparative Example 1 is low, and the peak shape is flat, indicating that the precursor does not remove components such as lignin and hemicellulose. The (002) peak intensity and peak shape sharpness of Comparative Examples 2 and Comparative Examples 3 exceed those of Comparative Example 1, but do not exceed those of Example 1, indicating that the synergistic effect of regulating the biomass precursor cannot be achieved without acoustic activation and oxidation treatment.

[0076] like Figure 3 As shown, Figure 3The XRD patterns of the hard carbon negative electrode materials after the treatment in step S500 of Example 1 and Comparative Examples 1-4 include (002) and (100) diffraction peaks, wherein the position of the (002) peak appears at 2θ=22°, and the corresponding interlayer spacing is about 4.037Å, and the position of the (100) peak appears at 2θ=45°, indicating that the material of the product prepared in Example 1 is hard carbon. The (002) peak of Example 1 is significantly shifted to the right, and the interlayer spacing is reduced, indicating that the degree of graphitization of the hard carbon negative electrode material is high, and the degree of order is enhanced, which can improve the conductivity of the hard carbon negative electrode material, while reducing the excessive growth of the electrolyte solid interface film and improving the first coulomb efficiency. And the peak intensity ratio of the (002) peak to the (100) peak is 2, that is, the (002) peak intensity is higher and the (100) peak intensity is weaker, indicating that the crystal layer structure of the sample is more layered and neatly stacked, and there is a strong diffraction signal in the direction perpendicular to the layer, indicating that the atomic arrangement in the plane is relatively irregular or disordered. The peak intensity ratio of 2 further indicates the orderliness of the interlayer arrangement of the hard carbon negative electrode material prepared in Example 1, that is, the product prepared in Example 1 has a certain degree of graphitization, and the hard carbon negative electrode material is successfully prepared. The (002) peak of Comparative Example 1 is not significantly shifted, and the degree of graphitization is low due to the failure to remove components such as lignin and hemicellulose. The (002) peak of Comparative Examples 3-4 has a certain right shift, and the interlayer spacing is reduced, indicating that the degree of graphitization of the hard carbon negative electrode material structure is improved compared with Comparative Example 1, but the effect of synergistic effect to regulate the biomass precursor cannot be achieved.

[0077] like Figure 4 As shown, Figure 4 This is a SEM image of the hard carbon negative electrode material after processing in step S500 of Example 1. The prepared hard carbon is mostly 50µm in size, with a small amount of lactic acid carbon balls attached and a porous structure etched on the surface. This porous structure can serve as a surface adsorption site and a sodium ion diffusion channel, thereby increasing the sodium storage sites and improving the rate performance.

[0078] like Figures 5 to 8 The first charge and discharge curves of the sodium ion battery of the hard carbon negative electrode material prepared in Examples 1 to 4 are shown, wherein the charge curve and the discharge curve both show a high-voltage slope area and a low-voltage platform-like area, and the first discharge specific capacity can reach 358.61 mAh / g, and the 1A / g discharge specific capacity can reach 330.61 mAh / g, which indicates that pretreatment of the biomass raw material with a mixed solution of an oxidant and an alkali solution can better hydrolyze to form wood cellulose, reduce the crystallinity of cellulose, and increase the degree of graphitization, and combined with organic acid salt coating and staged calcination, more optimized nanopore structures can be formed in the carbon material, increasing the specific surface area while reducing structural defects, thereby further etching the hard carbon negative electrode material, and more nanopore structures are more conducive to the storage of sodium ions.

[0079] like Fig. 9 and Fig.12 As shown, the charge and discharge curves of the products prepared in Comparative Examples 1 and 4 do not have a low-voltage platform-like region, indicating that Comparative Example 1 directly pre-carbonizes and subsequently treats the biomass raw materials and cannot completely hydrolyze the biomass raw materials, and does not coat the organic acid salt and gradient calcine the coated precursor, all of which result in the product after subsequent calcination not being graphitized hard carbon.

[0080] like Fig.10 and Fig.11 As shown, the charge and discharge curves of the products prepared in Comparative Examples 2 and 3 are relatively short in the low-voltage platform-like region, indicating that although the biomass raw materials can be hydrolyzed to a certain extent without acoustic activation treatment or alkaline solution treatment, the biomass raw materials cannot be completely hydrolyzed, thereby reducing the cellulose content in the biomass precursor, resulting in a decrease in the degree of graphitization, thereby affecting the electrochemical performance of the sodium ion battery manufactured based on the products of Comparative Examples 2 and 3.

[0081] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0082] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a biomass-derived hard carbon negative electrode material, characterized in that: The steps include: adding a biomass raw material and an oxidant into an alkaline solution to obtain a hydrolysis mixed solution; The hydrolyzed mixed solution is subjected to acoustic activation treatment, and then washed and dried in sequence to prepare a biomass precursor; The biomass precursor is sequentially pre-carbonized and pulverized to prepare low-temperature pyrolytic carbon; The low-temperature pyrolytic carbon is mixed with an organic acid salt to obtain a coating precursor, and the coating precursor is subjected to gradient calcination to obtain high-temperature pyrolytic carbon; The high temperature pyrolysis carbon is sequentially subjected to acid washing, water washing and drying to prepare the hard carbon negative electrode material; wherein: The gradient calcination includes a first gradient, a second gradient and a third gradient. The calcination temperature of the first gradient is the melting temperature of the organic acid salt, the calcination temperature of the second gradient is the reduction temperature or decomposition temperature of the metal oxide or metal carbonate, and the calcination temperature of the third gradient is the molding temperature of the hard carbon negative electrode material and the metal gasification temperature.

2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the organic acid salt to the low-temperature pyrolysis carbon is any value between 1wt% and 20wt%.

3. The method for preparing a hard carbon negative electrode material according to claim 2, characterized in that: The organic acid salt is a mixture of any one or more of gluconate, acetate, citrate or lactate.

4. The method for preparing a hard carbon negative electrode material according to claim 3, characterized in that: The gluconate is at least one of zinc gluconate, calcium gluconate, magnesium gluconate, potassium gluconate, ferrous gluconate, and magnesium gluconate; The acetate is at least one of zinc acetate, calcium acetate, potassium acetate and magnesium acetate; The citrate is at least one of zinc citrate, calcium citrate and potassium citrate; The lactate is at least one of zinc lactate, calcium lactate, potassium lactate and magnesium lactate.

5. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The mass ratio of the oxidant to the biomass raw material is any value between 3wt% and 10wt%.

6. The method for preparing a hard carbon negative electrode material according to claim 5, characterized in that: The oxidant is any one or more of hydrogen peroxide, hypochlorite and persulfate.

7. The method for preparing a hard carbon negative electrode material according to any one of claims 1 to 6, characterized in that: The concentration of the alkali solution is any value between 0.5 mol / L and 3 mol / L, and the temperature of the alkali solution is any value between 40° C. and 100° C.

8. The method for preparing a hard carbon negative electrode material according to claim 7, characterized in that: The alkali solution is an aqueous solution of one or more mixtures of metal hydroxides or metal carbonates.

9. The method for preparing a hard carbon negative electrode material according to claim 8, characterized in that: The biomass raw material is a mixture of any one or more of bamboo, wood, reed, coffee grounds, bagasse, wheat straw, rice straw, corn straw, rice sticks, coconut shell, durian shell, rice shell, hazelnut shell, starch, lignin, etc.

10. A sodium ion battery, characterized in that: A hard carbon negative electrode material prepared by the method for preparing a hard carbon negative electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Coating method for core-shell novel positive electrode material for lithium ion battery

    CN103474625A

  • Amorphous carbon material with multi-layer gradient microstructure as well as preparation method and application of amorphous carbon material

    CN114512646A

  • Hard carbon negative electrode material for sodium ion battery and preparation method of hard carbon negative electrode material

    CN114975929A

  • Lignin-based carbon-coated stannous sulfide composite material as well as preparation method and application thereof

    CN117154038A

  • Composite electrode material, and preparation method therefor and use thereof

    WO2024221949A1

Cited By

  • Pre-activated-carbonized lignin-based hard carbon as well as preparation method and application thereof

    CN120736520A

  • Hard carbon material coated with organic acid salt as well as preparation method and application of hard carbon material

    CN121020550A

  • Preparation method of porous hard carbon negative electrode material and application of porous hard carbon negative electrode material in sodium-ion battery

    CN121317701A